MANAGEMENT OF DIFFERENTIATED LEARNING IN PRIMARY SCHOOLS: A CASE STUDY - Imam Rohmanudin; Slamet Lestari; Maulida Ridani (Universitas Labuhanbatu, 2026)
Purpose – This study aims to analyze the management of differentiated learning based on the functions of educational management in elementary schools.Methodology – This research used a qualitative case study approach. This research was conducted at Al Azhar Islamic Elementary School 38 Bantul and Muhammadiyah Bodon Elementary School. The subjects of this study were school principals, vice principals for curriculum, and upper-class teachers. Data were collected through observations, in-depth interviews, and documentation studies. Data analysis was carried out using NVivo software, which included the stages of preparation, expression, coding, processing, data analysis, and report preparation.Findings – Findings of this study on the management of differentiated learning reveal the following: (a) Planning – Differentiated learning is incorporated into lesson planning through collaborative discussions in learning communities. Teachers design instructional strategies to accommodate diverse student needs, though further development of differentiated teaching modules is needed. (b) Organizing – The implementation of differentiated learning is supported by structured curriculum management and learning communities. These communities facilitate coordination among teachers to ensure alignment with learning objectives and student diversity. (c) Implementing – Differentiated learning is applied by adjusting teaching methods and classroom activities to match students’ varying abilities. The focus is primarily on process differentiation due to challenges related to class size and resource availability. (d) Evaluation – Routine evaluations, including supervision, teacher reflections, and collaborative meetings, assess the effectiveness of differentiated learning. The evaluation process also includes teacher development efforts to enhance instructional strategies and improve learning outcomes.Contribution – This study highlights the importance of differentiated learning management in supporting the Merdeka Curriculum, offering schools insights to enhance educational practices and outcomes.